VARIANTS OF NONSPECIFIC ULCERATIVE COLITIS COURSE IN CHILDREN: PREDICTION AND TREATMENT - E.N. Fedulova; O.A. Tutina; O.V. Fedorova; P.P. Potekhin; V.N. Kopeikin (Union of pediatricians of Russia, 2009)
Nonspecific ulcerative colitis has different masks, which make it hard for diagnostics. The course of the disease has many variants depending on the kind of therapy, its efficiency. prediction the course of the ulcerative colitis is very important to define the long term treatment management in order to increase the therapy efficiency and improve life quality.Key words: nonspecific ulcerative colitis, prediction the course of the disease, therapy, children.